Managing the water cycle in Kenyan small‐scale maize farming systems: Part 1. Farmer perceptions of drought and climate variability. (21st September 2015) - Muita, Richard R.; van Ogtrop, Floris; Ampt, Peter; Vervoort, R. Willem
Abstract : Farmer perceptions clearly influence the adoption of technology and adaptation to climate change, but may not be consistent with or captured by scientific measurements. There has been a significant research on how perceptions influence water resource management and adaptation to climate, but conclusions are unclear or contradictory. This research aimed to clarify what shapes perceptions and how this understanding can refine meteorological data collection and to make more relevant and useful tools for farmers to adapt to changes in the water cycle. A survey of 244 small‐scale maize farmers was conducted using a questionnaire and semi‐structured interviews in two districts in southern and western Kenya which differed in climate type and farming systems. Farmer perceptions of and adaptation to climate uncertainty were investigated and compared with meteorological data. Most farmers perceived changes in the patterns of rainfall and dry spells, including later onset of rains than in the past. They have already adjusted their management based on these perceptions, including later planting times. Despite this, analysis of meteorological data indicated no major trends in rainfall or dry spell patterns in the two regions. This research confirms that the perception that the water cycle is changing is based on a combination of climatic, economic, or social observations, and farmers are already changing their management to adapt to the perceived changes in climate. The article explores the reasons why these perceptions were inconsistent with the available meteorological data and suggests that research may improve the usefulness of meteorological data to farmers. WIREs Water 2016, 3:105–125. doi: 10.1002/wat2.1118 This article is categorized under: Human Water > Water as Imagined and Represented